Konsep Cinta dalam Novel Sunset Bersama Rosie karya Tere Liye: Kajian Psikologi Sastra Erich Fromm - Linda, Milfa Roza; Adek, Muhammad (Persona: Kajian Bahasa dan Sastra, 2024)
Pop novels are frequently undervalued due to their tendency to present a superficial and oversimplified portrayal of love. This research analyzed the depiction of love between characters in Tere Liye's novel Sunset Bersama Rosie (2017). Employing a content analysis methodology guided by Erich Fromm's theory, this study identifies five distinct concepts of love: love of neighbor, erotic love, love of God, love of self, and maternal love. The analysis uncovers a nuanced exploration of these concepts, particularly in the evolving relationships between the main characters. Notwithstanding its classification as a pop genre novel, Sunset Bersama Rosie offers an exceptionally diverse spectrum of love, showcasing a depth that is uncommon within the genre.